The Effects of Light Color on Seed Germination of Markhamia stipulata (Wall.) Seem - Rahmawati, Sri Ulie; Rachmadiyanto, Arief Noor (KnE Life Sciences, 2017)
Markhamia stipulata (Wall.) Seem. (Bignoniaceae) is one of collections in Bogor Botanical Garden that potential as a medicine. Information about germination of these species were not known yet. This research was aimed to examine the effect of light color on germination process of Markhamia stipulata (Wall.) Seem. The research method used a Randomized Complete Block Design (RCBD) that consist of three treatments (red light, far red light, dark) and one control (open air) with four replications for each group. Each group consist of 10 seeds. Precentage of seed germination; seedling height; cotyledon width; length, width and number of leaves were measured. The result showed that seed germination start at third day after sowing. Germination rate and germination rate coefficcient showed there is no significant difference between all treatments even though far red light showed highest number (100 %; 0.755). However, light color influence on seedling growth. Far red light showed affect on internodes distance. Dark light showed affect on leaves and cotyledon size. Red light and control showed similarity. Keywords: dark; far red light, Markhamia stipulata (Wall.) Seem; red light; seed germination